Manajemen Pengelolaan Sampah Berbasis Sedekah: Studi Kasus di MI Al Ma’arif 02 Ciklapa Kabupaten Cilacap - Imam Mahrus (Balai Diklat Keagamaan Semarang, 2025)
The goal of this activity is to create a waste-free madrasa environment while providing benefits to students. The methods used include education, action, which includes collection, sorting, sales, re-organization, and finally evaluation. This activity is carried out at least twice a day: in the morning after all classes have been conducive. Meanwhile, the afternoon activity is carried out after students have returned home. The collected waste is then sold and the proceeds are donated to orphaned and underprivileged students. With perseverance and seriousness, the waste management effort has finally borne fruit. A positive response from other madrasa residents and street vendors selling around the madrasa has begun to be seen. They are willing to help manage the waste. Such conditions certainly greatly assist the Madrasa Principal's activities in managing waste. The results are quite significant, as evidenced by the fact that to date, 12 (twelve) orphaned and underprivileged students have received alms from this activity with a total nominal value of Rp935,000.00 (nine hundred and thirty-five thousand rupiah).